2009
DOI: 10.1111/j.1468-3083.2009.03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of psoriatic onychodystrophy by a water‐soluble nail lacquer

Abstract: In our experience, the new water-soluble nail lacquer proved to be effective in decreasing signs and symptoms of nail dystrophy in psoriatic patients. The effect was particularly evident on NAPSI and on pitting. The product was very well accepted by the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…As a consequence, a number of pharmaceutical nail lacquers, such as Penlac ® (containing ciclopirox), Loceryl ® (containing amorolfine), Onytec ® (containing ciclopirox), Kerydin™ (containing tavaborole), Jublia ® (containing efinaconazole) are commercially available for the topical treatment of onychomycosis. Much research into the formulation of pharmaceutical nail varnish is also ongoing, for example, thermogelling lacquers [7], bilayered lacquers [8], phase-separating lacquers [9], and those containing hydrosoluble polymers [10], econazole [11], terbinafine [12], clotrimazole [13], clobetasol [14], natural products [15,16] and urea [17], among others.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a number of pharmaceutical nail lacquers, such as Penlac ® (containing ciclopirox), Loceryl ® (containing amorolfine), Onytec ® (containing ciclopirox), Kerydin™ (containing tavaborole), Jublia ® (containing efinaconazole) are commercially available for the topical treatment of onychomycosis. Much research into the formulation of pharmaceutical nail varnish is also ongoing, for example, thermogelling lacquers [7], bilayered lacquers [8], phase-separating lacquers [9], and those containing hydrosoluble polymers [10], econazole [11], terbinafine [12], clotrimazole [13], clobetasol [14], natural products [15,16] and urea [17], among others.…”
Section: Introductionmentioning
confidence: 99%
“…This water-based HPCH solution forms a protective film that remineralizes and restructures nails, protects keratin, and maintains hydration. In clinical studies, it has been shown to reduce the signs of fragility and roughness in the nails of patients with psoriatic nail dystrophy (7)(8)(9). The HPCH-based nail solution is not intended as a cure for onychomycosis, as it does not exhibit antifungal activity; instead, it is able to form a film on the nail surface that may prevent fungal invasion.…”
mentioning
confidence: 99%
“…In the literature, multiple treatments have been proposed, with topical and intralesional corticosteroids being the first line of choice [6], as it was done in the case of our patient who had infiltrations with triamcinolone but with a few response, probably due to the extensive involvement of the nail bed.…”
Section: Discussionmentioning
confidence: 99%